Answer:
![2\sqrt{2} \\2](https://tex.z-dn.net/?f=2%5Csqrt%7B2%7D%20%5C%5C2)
Step-by-step explanation:
![\sqrt{8} = \sqrt{4*2} = \sqrt{4} * \sqrt{2} = 2*\sqrt{2} = 2\sqrt{2} \\\\\sqrt[3]{8} = \sqrt{2*2*2} = 2](https://tex.z-dn.net/?f=%5Csqrt%7B8%7D%20%3D%20%5Csqrt%7B4%2A2%7D%20%3D%20%5Csqrt%7B4%7D%20%2A%20%5Csqrt%7B2%7D%20%3D%202%2A%5Csqrt%7B2%7D%20%20%3D%202%5Csqrt%7B2%7D%20%5C%5C%5C%5C%5Csqrt%5B3%5D%7B8%7D%20%3D%20%5Csqrt%7B2%2A2%2A2%7D%20%20%3D%202)
Answer:
There is<em> no solution</em> to this problem.
Step-by-step explanation:
In order to find the solution, y or x needs to be shown.
That would be an acute triangle because all the angles are less than 90 degrees I hoped this helped
<em>y</em> - 1/<em>z</em> = 1 ==> <em>y</em> = 1 + 1/<em>z</em>
<em>z</em> - 1/<em>x</em> = 1 ==> <em>z</em> = 1 + 1/<em>x</em>
==> <em>y</em> = 1 + 1/(1 + 1/<em>x</em>) = 1 + <em>x</em>/(<em>x</em> + 1) = (2<em>x</em> + 1)/(<em>x</em> + 1)
<em>x</em> - 1/<em>y</em> = <em>x</em> - (<em>x</em> + 1)/(2<em>x</em> + 1) = (2<em>x</em> ² - 1)/(2<em>x</em> + 1) = 1
==> 2<em>x</em> ² - 1 = 2<em>x</em> + 1
==> 2<em>x</em> ² - 2<em>x</em> - 2 = 0
==> <em>x</em> ² - <em>x</em> - 1 = 0
==> <em>x</em> = (1 ± √5)/2
If you start solving for <em>z</em>, then for <em>x</em>, then for <em>y</em>, you would get the same equation as above (with <em>y</em> in place of <em>x</em>), and the same thing happens if you solve for <em>x</em>, then <em>y</em>, then <em>z</em>. So it turns out that <em>x</em> = <em>y</em> = <em>z</em>.
Answer:
A
Step-by-step explanation:
Work with the two points
Formula
m = (y2 - y1)/(x2 - x1)
Givens
y2 = 3
y1 = 1
x2 = - 2
x1 = - 5
Solution
m = (3 - 1) / (-2 - - 5)
m = 2 / (-2 + 5)
m = 2 / 3
Answer: A